Model of Linear Quadratic Regulator (LQR) Control System in Waypoint Flight Mission of Flying Wing UAV - Priyambodo, Tri Kuntoro; Dhewa, Oktaf Agni; Susanto, Try (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2020)
The ability of the aircraft to trace the waypoint trajectory is a major requirement for the completion of various missions. However, the magnitude of steady state error and multiple overshoot caused by environmental disturbances can cause instable motion of the aircraft. Such conditions can make the aircraft experience a shift and change its direction from a predetermined path. Therefore, in this study Linear Quadratic Regulator (LQR) control method is applied to minimize steady state error and multiple overshoot. The LQR control method has the ability to maintain the stability of the aircraft and produce minimum errors. Besides, the LQR control method can also be modified by providing input references so that it can be used for tracking trajectories. System testing is done directly on tracing the triangular trajectory pattern to find out directly the functioning of the system. The results derived from the testing of the model design indicated a steady state tendency of 3.55% error, with the largest deviation of 10.55% and 83% accuracy for tracking from the first waypoint to the second waypoint. It was also reported a steady state tendency of 2.88% error, the largest deviation of 7.28% with 93% accuracy for tracing from the second waypoint to the third waypoint.